FEATURES OF DENTAL CARE REFORM IN UKRAINE (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the transformation of the dental care delivery system in Ukraine in the context of healthcare reform. The regulatory and legal foundations of the medical reform are examined, including changes in the financing model, the establishment of the National Health Service of Ukraine, as well as the impact of decentralization processes on the management of dental care institutions. The study reveals the specific features of the redistribution of powers between central executive authorities and local self-government bodies in the organization of dental care services. The main organizational and legal models of the functioning of the dental sector are analyzed, including the reorganization of state and municipal institutions into municipal non-profit enterprises, the development of the private sector, and the expansion of mixed forms of dental service provision. It is established that the reduction of public funding for dentistry, the decrease in the number of municipal institutions, and the weakening of human resources have led to reduced accessibility of dental care for socially vulnerable population groups, primarily children, the elderly, and rural residents, thereby intensifying the issue of social inequality in healthcare. The existence of managerial and legal imbalances between the declared objectives of the reform and the actual mechanisms of their implementation at the local level is substantiated. Particular attention is paid to the problems of preventing dental diseases, the fragmented nature of regional programs, and the absence of a comprehensive state strategy for the development of dental care. The role of digitalization and the implementation of the electronic healthcare system (eHealth) in enhancing the transparency of management processes, accounting for dental services, and improving the quality of managerial decision-making is analyzed. The article concludes that there is a need to improve public policy in the field of dentistry, taking into account the principles of social justice, accessibility, preventive orientation, compliance with European healthcare standards, and the needs of the population.